World Englishes in Expanding Circle: Views from University Students in Thailand and China - Weerachairattana, Rotubon; Duan, Jun; Buripakdi, Adcharawan (Journal of Studies in the English Language, 2019)
Diverse forms of English have emerged in all domains of the society. Due to the change in status of English and the growing acceptance of World Englishes (WE) in ELT, this study aimed to explore how university students in the expanding circle perceived and positioned themselves toward WE. 255 students participated in this study, including 125 Thai university students in Thailand and 130 Chinese university students in China. Data were collected from a questionnaire to explore their perceptions and a semi-structured interview to elicit their positions. The questionnaire data were analyzed in terms of frequency while the interview data were coded and analyzed based on Buripakdi (2008; 2012). The questionnaire revealed that there were similarities and differences in the perceptions of Thai and Chinese respondents regarding WE. Besides, five positions toward WE emerged from the interview i.e. the Standard English, the Instrumental English, the Glocal English, the World Englishes, and the Situational English. These findings reflected the hegemony of British and American English, the place of native and non-native varieties in the real context of use, the potential of Thai and China English as varieties of WE, and the coexistence of standard Englishes and WE in ELT.